Intersexual Resource Competition and the Evolution of Sex-Biased Dispersal - Li, Xiang-Yi; Kokko, Hanna (Frontiers in Ecology and Evolution, 2019)
Resource competition is a major driver of dispersal: an emigrating individual leaves more resources to its kin. Existing models of sex-biased dispersal rarely consider intersexual competition for resources. Instead, male reproductive success is often solely assumed to depend on female availability, implying a tacit assumption that male presence never depletes resources, such as food, that are of interest to female kin. In reality, both male and female offspring typically consume resources on their natal site before departing to consume resources elsewhere, and sexually dimorphic body sizes imply that the resource needs can differ. The goal of our study is to investigate how intersexual competition for resources can affect the evolution of sex-specific dispersal, via competition between kin of the same sex or different sexes and the subsequent success elsewhere. Our individual-based simulation model allows not only the dispersal probability but also its timing to evolve. We consider dispersal timing because later dispersal yields a longer period of kin competition than dispersal that occurs soon after independence. We also highlight the role of sex-specific income/capital breeding strategies, which is understudied in both empirical and theoretical literature of sex-specific dispersal. We show that sex biases in dispersal probability and timing are sensitive to the presence of intersexual competition, sexual differences in capital vs. income breeding strategies, and sexual dimorphism in the quantity of resources consumed. Males may evolve to disperse earlier if they also consume more food, as a result of selection to reduce intersexual kin competition. Alternatively, males may evolve to disperse less as well as later than females, if male fitness depends more on resource accumulation (e.g. building a large body to succeed in mating competition under polygyny) whereas female fitness depends more on reliable income (e.g. in species that require extended periods of maternal foraging), even if both sexes are equally competitive in consuming resources. Although the more dispersive sex is often the earlier departing sex, we also find cases where the only clear dimorphism is found in dispersal timing. We thus encourage more studies on the timing aspect of sex-biased dispersal.